Pengaruh Kesiapan Belajar dan Konsep Diri Terhadap Hasil Belajar Mahasiswa Pendas (Studi Pada Pokjar Sidrap) - Subirman Musa; Muh. Alwi; Basmi Basmi; Muh. Ali (Jurnal Sinestesia, 2022)
This study aims to (i) determine the effect of learning readiness on student learning outcomes at UPBJJ UT Makassar, pokjar Sidrap; (ii) knowing the effect of self-concept on student learning outcomes at UPBJJ UT Makassar, pokjar Sidrap; and (iii) knowing the effect of learning readiness and self-concept simultaneously on student learning outcomes at UPBJJ UT Makassar, pokjar Sidrap. The research method uses a quaternative approach and is classified into the type of ex post facto research. The technique of collecting data through primary data comes directly from the research subject. The population is 530 students at Universitas Terbuka, Pokjar Sidrap students. The sampling technique used was random sampling in order to obtain 201 samples. The data analysis technique used is descriptive analysis, path analysis requirements test, and hypothesis testing. The results showed that learning readiness had a significant effect on student learning outcomes at UPBJJ UT Makassar pokjar Sidrap; self-concept has a significant effect on student learning outcomes at UPBJJ UT Makassar, pokjar Sidrap; Learning readiness and self-concept simultaneously have a significant effect on student learning outcomes at UPBJJ UT Makassar, pokjar Sidrap.